ANALISIS PENGARUH MOTIVASI DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASI DI PTUN - Annisa Amalia; Mella Yunita; Evalinapkapahan Evalinapkapahan (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The purpose of this study was to determine the influence of job satisfaction and work motivation which is directly related to organizational commitment. Job satisfaction and work motivation felt by employees can reduce the value of organizational commitment. Employees who are satisfied with the work they get will be motivated to increase their commitment so that it will have an impact on the implementation of organizational commitment at the Medan State Administrative Court. This study was conducted at the Medan State Administrative Court on job satisfaction towards organizational commitment at the Medan State Administrative Court. This study aims to test the influence of job satisfaction and work motivation on organizational commitment. The number of samples determined was 50 respondents using the research method. As independent variables are job satisfaction and work motivation, while the dependent variable is organizational commitment. The analytical tools used include validity tests, reliability tests, multiple linear regression analysis and hypothesis testing used is a partial test (t test). The results of hypothesis testing show that the first hypothesis (H1) and the second hypothesis (H2) are accepted. The results of testing the first hypothesis (H1) obtained the results that job satisfaction has a positive and significant effect on organizational commitment. These results Testing the second hypothesis (H2) obtained the results that work motivation has a positive and significant effect on organizational commitment. Motivation and job satisfaction have a simultaneous influence on organizational commitment, contributing 46.3%, while the remainder is influenced by unknown variables.